A comparative study of public primary teacher education in Afghanistan and the Philippines - Ahmadzai, Mohammed Yunus 1938- (s.n.], 1970)
The main purpose of the study is to compare the system of primary teacher education in Afghanistan and in the Philippines. It aims to serve as basis for recommending some of the good features of the system of primary teacher education in the Philippines to the system of primary teacher education in Afghanistan. These features may be in terms of objectives, administration and organization, and curricular and co-curricular programs of the primary education